Motivational spheres of student youth in modern russian society: educational and research - Kolesnikova, Galina I.; Barkova, Eleonora Vl.; Oparina, Nina A.; Vlasova, Victoria N.; Potapkina, Ekaterina V.; Panov, Maksim O. (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The article analyzes the elements that make up the motivational field of student youth and determine its specificity in the context of the modern realities of Russian society. The subject of the research is the content filling of such elements of the motivational field in the basic directions of activity in the youth environment as the choice of a profession, the motives of interpersonal communication, the structure of extracurricular interests, and the motives for choosing a hobby, a spouse. The theoretical foundation of the research is the works of domestic and foreign authors of the socio-philosophical and sociological directions. Based on the goal and objectives, the work uses comparative analysis, interdisciplinary synthesis and other techniques of general scientific methodology. Based on the results obtained, it can be concluded that most higher education students have the ratio of biological and psychological age within the age norm.